2019
DOI: 10.1111/papr.12777
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pain Service: A 10‐Year Experience

Abstract: Background Pain management after surgery is crucial to decrease perioperative morbidity and mortality. Acute pain services (APS) are multidisciplinary teams that represent a modern strategy to address pain inside hospitals. The APS defines and applies pain treatment protocols specific for each surgery. To evaluate the performance of the APS at our institute, we performed a large retrospective cohort study focusing on complications of epidural analgesia and IV opiates. Methods Data from the 10 years of activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…These effects were paralleled by an improvement in the quality of sleep. The length of hospital stay was comparable to that observed with IV-PCA in our Acute Pain Service experience 20…”
Section: Discussionsupporting
confidence: 77%
“…These effects were paralleled by an improvement in the quality of sleep. The length of hospital stay was comparable to that observed with IV-PCA in our Acute Pain Service experience 20…”
Section: Discussionsupporting
confidence: 77%
“…A series of studies showed that pain intensity and pain relief were highly skewed data that cannot be appropriately reported as means (Moore et al, 2010;Moore et al, 2011). This was confirmed in the 10-year experience of acute pain service in Italy, in which the mean VAS was relatively low in clinical practice because most patients achieved satisfactory pain relief (Deni et al, 2019). Therefore, the percentage and pain intensity of patients with VAS >3 were concealed by the mean VAS; these populations were inclined to withdraw from clinical trials due o analgesic failure, which introduced bias.…”
Section: Discussionmentioning
confidence: 95%
“…Although there is a shift towards using more oral and regional analgesia, PCA opioids remains a commonly used analgesic technique [ 22 ]. A survey of over 17000 patients from an acute pain service found that 52% of patients used PCA opioids, while another survey found that PCA was used in 79% of hospitals in Germany [ 23 , 24 ]. PCA opioid is recommended when parenteral opioids are required [ 25 ].…”
Section: Discussionmentioning
confidence: 99%